EUROPEAN POSITION ON CLINICAL PRACTICE OF EXTRACTION AND NONEXTRACTION THERAPY IN ORTHODONTICS - V. D. Kuroiedova; A.V. Petrova; Y.V. Rud (Проблеми екології та медицини)
Orthodontic treatment is a long-lasting and difficult process which requires compliance between doctor and patient. It is a complex process, duration of which increases with transition from temporary to permanent bite. The main factor of orthodontic treatment is the cost of the procedure because there are new and modern tools and equipment. There are several ways to reduce orthodontic treatment: in the period of changing teeth, these are methods of corrective teeth extraction, based on the difference in the mesial-distal dimensions of milk (temporary) molars and method Hotz, replacing them with premolars, is the removal of individual healthy teeth according to the chosen treatment strategy bite disorders, compact osteotomy, the use of various physiotherapeutic methods without drugs and with the use of agents that promote bone tissue relaxation in combination with active physical factors and others related to the improvement of orthodontic appliances. The most significant factor in orthodontic treatment, resulting in a number of cases of interrupting the correction process, is its duration, up to 2-3 years in the period of permanent teeth. One more serious problem in orthodontic treatment associated with strategic choice of extraction or nonextraction method of treatment is stability of received clinical results. Only therapeutic prognosis of stabile morphological and functional clinical advantages of orthodontic treatment can be a basis for choice of orthodontic treatment management with the use of extraction of some healthy teeth. So, the problem of orthodontic treatment both in children and adults is one of the most important in bite correction. That’s why surgeries are involved in complex orthodontic treatment. Extraction of some permanent teeth is coordinated decision between patient and orthodontist considering the number of factors. Orthodontist must be theoretically competitive in the peculiarities of child’s organism. Despite the use of surgery of healthy teeth in orthodontic treatment in European and scientific literature the choice of extraction and nonextraction method of treatment has been yet discussable. New diagnostic methods, modern orthodontic appliances, national peculiarities of face and other features are needed for correct European thought in orthodontist.